The Desugn of MACPAC - A Graphics Subroutine Library Based on a Design Philosophy for the Next Generation of Graphics Packages - Vrenjak, Helen (My University, 1984)
This paper presents the design of a graphics subroutine library, MacPac, as a contribution to the development of a standard for future graphics packages. The need for a new graphics standard, and hence the motivation for the development of MacPac, is illustrated through a detailed discussion of existing graphics standards and systems. MacPac is based on a design philosophy developed by Mark Green for the next generation of graphics packages. It addresses the hardware and software ideas of the 80's, incorporating and building upon the valuable and tested ideas of a number of existing graphics systems. The design languages used in the development of MacPac were created by Mark Green for the design of user interfaces. This work examines the effectiveness of these languages in the design of a graphics system.
Keywords: graphics; subroutine library; design philosophy; next generation